The dig [videorecording (DVD)] - Taaffe, Emily; Magee, Francis; Cranitch, Lorcan; Dunford, Moe (Electric Entertainment, 2019)
A father, Sean McKenna, becomes obsessed with finding the body of his murdered daughter, Niamh. The murderer, Ronan Callahan, is released from jail after serving a 15-year sentence, having no memory of his crime. At first, he wants Sean off his land, but then decides to help dig for Niamh's missing body in the bog. He pours the old alcohol in his house down the drain, but eventually drinks shots in a pub, hoping to remember the act of murder and where he buried the girl. Ronan eventually remembers a detail that reveals what really happened.